Analisis Strategi Pencegahan Korupsi Menurut Perspektif Hukum Islam Dalam Implementasi Asas Legalitas Tindak Pidana: Hukum Islam dalam konteks Pencegahan Korupsi - BR PA, Esra Julita; Gaby Agustina Nainggolan; Desy Yolanda Br Bangun; Syuratty A Rahayu Manalu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Corruption has become a global concern in efforts to strengthen good governance. In the context of Islamic law, aspects of preventing corruption and implementing the principle of legality in criminal acts attract in-depth attention. This article analyzes corruption prevention strategies from the perspective of Islamic law in the context of applying the principle of legality to criminal acts. The method in this research is a qualitative method in exploring Islamic legal concepts related to preventing corruption, such as Taqwa, Adl, and Amanah,as well as how these values ​​can be applied in efforts to prevent and overcome corruption. Furthermore, this article also examines legal aspects related to the implementation of the principle of legality in enforcing the law against criminal acts of corruption according to Islamic teachings. The results of the analysis show that the principles of Islamic law provide a strong foundation for corruption prevention strategies. Concepts such as justice, transparency, fair punishment, and building strong institutions are the main focus in overcoming the problem of corruption. In the context of implementing the principle of legality, consistency with sharia principles in establishing and enforcing laws is crucial to ensure the success of efforts to prevent corruption. This article contributes to a better understanding of corruption prevention strategies from an Islamic legal perspective, as well as the importance of integrating Islamic legal values ​​and principles in efforts to eradicate corruption. The practical implications of this analysis support the need for a holistic approach that includes legal and moral aspects in tackling corruption to create a society that is more just and has integrity.